Participação do inflamossoma NLRP 3 e dos receptores purinérgicos na hiperalgesia visceral da pancreatite alcoólica experimental - Girão, Deysen Kerlla Fernandes Bezerra (2017)
One of the most important symptoms of pancreatitis is the abdominal pain, which usually signals a need for care in health services. Much pathophysiology of this phenomenon is still not understood. It is known that a pancreatitis initiates a cascade of activation of inflammatory mediators, which occur in a sterile way, through the action of molecules recognition damage associated molecules pattern (DAMPs), among them the ATP. Activation of NLRP 3 inflammassome is one of the possible pathways to be triggered by DAMPs, with the P2X7 receptor being one of the components of this pathway. Several studies have showed the evidence of interest in this type of inflammassome in pancreatitis, but the nociceptive changes have not yet been investigated. This work sought to evaluate the role of the inflammassome NLRP 3 in the visceral nociception in alcoholic pancreatitis, as well as the involvement of the purinergic receptors. For this, acute pancreatitis was induced in Swiss mice (25-30g) by two intraperitoneal injections of ethanol (1.35g/kg), associated or not to palmitoleic acid (POA) (150 mg/kg), with an interval of 1h. Controls received either ethanol or saline. A curve of variation of weight and survival was evaluated as markers of animal welfare. Subsequently, the temporal course of inflammation was investigated by the histopathological analysis, the serum amylase lipase level and the myeloperoxidase (MPO) measurement of the pancreas. Visceral hyperalgesia was also evaluated through the Von Frey test. By 24-h, the levels of pro-inflammatory pancreatic cytokines (IL-1β, MCP-1, TNF-α and IL-6) and markers of oxidative stress markers (plasma MDA and pancreatic GSH) were measured. The involvement of mast cells and macrophages in nociception was evaluated by depletion of these cells. Modulation of nociception by purinergic receptors was investigated through the use of antagonists: PPADs (non-specific for P2) and BBG (selective for P2X7) given intravenously 30 minutes prior to 24-h evaluation after induction of pancreatitis. The effect of BBG in the CNS was over assessed by intrathecal administration of this drug. Influence of components of inflammassome NLRP 3 was evaluated by the use of C57BL (20-25g) knockout mice for caspase-1, NLRP 3, ASC, IL-1R and IL-18. The results showed that the association between ethanol and POA causes a decrease in the mice's well-being, with significant weight variation and a reduction in survival to 64.7%. Alcoholic pancreatitis caused histopathological changes and increased serum levels of pancreatic enzymes, MPO, pro-inflammatory cytokines and oxidative stress. These changes occurred with visceral hyperalgesia (ethanol + POA: 3.29 ± 0.45 g, saline: 15.35 ± 0.82 g,). Macrophages and mast cells are important for the occurrence of hyperalgesia, with the increase of nociceptive thresholds increasing by 28% and 29%, respectively, by cell depletion. The non-specific blockade of purinergic receptors (ethanol + POA + PPADS 12.5 mg / kg: 9.38 ± 2.30 g, ethanol + POA: 4.4 ± 0.45 g) and specific blockade of P2X7 (ethanol + POA + BBG 50 mg / kg: 8.14 ± 0.50 g, ethanol + POA: 3.35 ± 0.49 g) decreases nociception. This effect was still maintenance by with intrathecal administration (ethanol + POA + BBG: 8.47 ± 0.92 g, ethanol + POA: 3.52 ± 1.08 g). It has been shown that a deletion of components of inflammassome NLRP 3 (Caspase-1, NLRP 3, ASC, IL-1R and IL-18) reduced visceral hyperalgesia, showing that this pathway an important role in this phenomenon. We conclude that hyperalgesia in acute pancreatitis involves a participation of the purinergic receptors, occurring, at least partially, through the involvement of the inflammassome NLRP 3. In addition, we have shown that macrophages and mast cells contribute significantly to visceral nociception associated to pancreatitis.